Hypoxia re-programs 2′-O-Me modifications on ribosomal RNA - Metge, Brandon J. (iScience, 2020)
Hypoxia is one of the critical stressors encountered by various cells of the human body under diverse pathophysiologic conditions including cancer and has profound impacts on several metabolic and physiologic processes. Hypoxia prompts internal ribosome entry site (IRES)-mediated translation of key genes, such as VEGF, that are vital for tumor progression. Here, we describe that hypoxia remarkably upregulates RNA Polymerase I activity. We discovered that in hypoxia, rRNA shows a different methylation pattern compared to normoxia. Heterogeneity in ribosomes due to the diversity of ribosomal RNA and protein composition has been postulated to generate “specialized ribosomes” that differentially regulate translation. We find that in hypoxia, a sub-set of differentially methylated ribosomes recognizes the VEGF-C IRES, suggesting that ribosomal heterogeneity allows for altered ribosomal functions in hypoxia.